1997
DOI: 10.1016/s0969-2126(97)00212-8
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of the sodium channel antagonist conotoxin GS: a new molecular caliper for probing sodium channel geometry

Abstract: This is the first three-dimensional structure of a 'four-loop' sodium channel inhibitor, and it represents a valuable new structural probe for the pore region of voltage-dependent sodium channels. The distribution of amino acid sidechains in the structure creates several polar and charged patches, and comparison with the mu conotoxins provides a basis for determining the binding surface of the conotoxin GS polypeptide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 56 publications
0
39
0
Order By: Relevance
“…The three-dimensional structure of HNTX-IV has little resemblance to the three-loop -conotoxins (GIIIA/B and PIIIA) in agreement with the low sequence identity between them and their different cystine frameworks (27,40,41). Unlike the three-loop -conotoxins, both conotoxin GS and HNTX-IV belong to the inhibitor cystine knot structural family with the same disulfide bond pattern despite little sequence identity (42). Fig.…”
Section: Effects Of Synthetic Analogues On Sodium Channel Currents-thmentioning
confidence: 55%
“…The three-dimensional structure of HNTX-IV has little resemblance to the three-loop -conotoxins (GIIIA/B and PIIIA) in agreement with the low sequence identity between them and their different cystine frameworks (27,40,41). Unlike the three-loop -conotoxins, both conotoxin GS and HNTX-IV belong to the inhibitor cystine knot structural family with the same disulfide bond pattern despite little sequence identity (42). Fig.…”
Section: Effects Of Synthetic Analogues On Sodium Channel Currents-thmentioning
confidence: 55%
“…Studies of -conotoxin GIIIA suggested that the largest activity loss was introduced when Arg-13 or Arg-19 was replaced (36). Conotoxin GS binds competitively with -conotoxin GIIIA to the sodium channel surface (site I), but these two conotoxins have little sequence and structure identity with one other (38,39). Unlike -conotoxins, both conotoxin GS and HNTX-IV adopt a cystine-knot motif with the same disulfide bond pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Conotoxin GS (38,39), -conotoxin PIIIA (6), -conotoxin GIIIA (7,35,36), and -conotoxin GIIIB (8, 37) block at site I. HWTX-I was suggested to be an N-type calcium channel inhibitor (33). Like HWTX-IV and conotoxin GS, it adopts a 1-4, 2-5, 3-6 disulfide pattern and cystine knot motif (32).…”
Section: Fig 4 Comparison Of Amino Acid Sequence Of Hwtx-iv With Hwmentioning
confidence: 99%
“…geographus Fainzilber et al, 1995c;McIntosh et al, 1995;Safo et al, 2000;Daly et al, 2004;Zorn et al, 2006 Fainzilber et al, 1995b;Fainzilber et al, 1995c;McIntosh et al, 1995;Ekberg et al, 2006;Zorn et al, 2006 C. geographus Conotoxin Yanagawa et al, 1988;Hill et al, 1997 P, fish; M, molluscs; V, worms; *, C-terminal amidation; N.D., not determined; TTX-S TTX-sensitive; TTX-R, TTX-resistant.…”
Section: Speciesmentioning
confidence: 99%
“…Conotoxin GS was identified as an O-superfamily conotoxin; however, in contrast to MrVIA and MrVIB, conotoxin GS seems to share a binding site with TTX and GIIIA, suggesting that this conotoxin is distinct both in structure and mode of action (Yanagawa et al, 1988;Hill et al, 1997). In addition, two novel O-superfamily conotoxins, LtVIC and LtVIIA, were identified from Conus litteratus using a DNA-sequencing approach (Pi et al, 2007;Wang et al, 2008).…”
Section: Other Conotoxin Inhibitors Of Voltage-gated Sodium Channelsmentioning
confidence: 99%